SOCIAL MARKETING ASPECT IN ANTI-VIOLENCE AGAINTS WOMEN CAMPAIGN IN INDONESIA - Yuanita Safitri; Mia Angeline (IAIN Salatiga, 2019)
This article aims to answer how anti-violence against women campaigns and social marketing aspects are carried out by the four selected institutions or communities in 2016-2018 period. The four institutions chosen were UN Women, the Alliance of New Men, Indonesian OBR, and The National Commission on Violence Againts Women. The four institutions were chosen because they were considered as the most active institutions or communities in voicing the issue through online media. This research used descriptive qualitative approaches and case study methods. The result shows that the anti-violence against women campaign from four institutions is included in the social marketing concept and uses the marketing mix. Products sold are not like the commercial marketing, but the 16 Days Anti Violence Against Women event, and information to the target audiences. The price concept used is non-monetary incentives, and the distribution channels used are quite diverse, both online and offline.